Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 619487 species occurrences available in GBIF matching the query: { "and" : [ "HasGeospatialIssue is false", "Geometry POLYGON((-82 -33,-82 3,-26 3,-26 -33,-82 -33))", "Year is greater than or equal to 2012" ] } The dataset includes 619487 records from 89 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0003825-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences